Long-term changes of body composition in an elite soccer player and its association with cognition: a ten-year retrospective study - Cavedon, V.; Milanese, C.; Rusciano, A.; Corradini, G.; Zancanaro, C. (Medicina dello Sport, 2021)
BACKGROUND: In soccer, understanding of long-term body composition changes associated with training and competition would be useful for both players and coaches. However, studies of this kind are hampered by frequent inter-club transfer, changes in club policy or continued availability of the relevant facilities. METHODS: In this work we tracked lean and fat mass of an elite soccer player along ten consecutive years by means of dual-energy X-ray absorptiometry, which was carried out at preseason, mid-season, and end-season. Cognitive performance was also evaluated. RESULTS: Correlation analysis showed that whole-body and regional fat mass increases with age (P=0.009 or less). Repeated measure ANOVA showed that whole-body lean soft tissue mass tended to cycle along the competitive season (P=0.059) with an increase at mid-season and, to a lesser extent, end-season vs. preseason. Fat mass and lean soft tissue mass respectively increased (P=0.018) and tended to decrease (P=0.083) during off-season. Several seasonal changes in body composition were statistically meaningful (i.e., >least significant change). Average reaction time in visual attention task test increased with fat mass (r=0.866, P=0.001). CONCLUSIONS: These novel results highlight body composition trajectories and their relationship with cognition in an elite soccer player.